Extension in distribution of Raorchestes parvulus (Boulenger, 1893) (Anura: Rhacophoridae) to China - Yu, Guohua; Liu, Shuo; Hou, Mian; Li, Song; Yang, Junxing (Zootaxa, 2019)
We record Raorchestes parvulus (Boulenger, 1893) for the first time from China based on six specimens collected from southern Yunnan. Phylogenetically these individuals were placed in a clade with R. parvulus from Southeast Asia and pairwise genetic distances in DNA sequences of the mitochondrial 16S rRNA gene ranged from 0 to 3.1% within the clade. Morphologically these specimens agree with R. parvulus in a series of characters including body size small, a large external vocal sac, vomerine teeth absent, snout slightly shorter than the diameter of the orbit, canthus rostralis indistinct, interorbital space broader than the upper eyelid, tympanum indistinct, fingers free, toes webbed at the base, an inner metatarsal tubercle, tibio-tarsal articulation reaches eye, small warts on the dorsal surfaces of body and limbs, throat smooth, belly granular, a dark triangular blotch between the eyes, a butterfly-like dark band on the back, a dark blotch on each side of lumbar region, and more or less distinct dark bars across limbs. Obvious intraspecific variation in the color pattern occurs within the population. It is possible that previous records of Raorchestes longchuanensis (Yang and Li, 1979) from southern Yunnan might be misidentification of R. parvulus.